Hypoxic pulmonary vasoconstriction, carotid body function and erythropoietin production in adult rats perinatally exposed to hyperoxia. (15th May 2015) - Prieto‐Lloret, Jesus; Ramirez, Maria; Olea, Elena; Moral‐Sanz, Javier; Cogolludo, Angel; Castañeda, Javier; Yubero, Sara; Agapito, Teresa; Gomez‐Niño, Angela; Rocher, Asuncion; Rigual, Ricardo; Obeso, Ana; et al.
Abstract : Key points: Adult animals that have been perinatally exposed to oxygen‐rich atmospheres (hyperoxia), recalling those used for oxygen therapy in infants, exhibit a loss of hypoxic pulmonary vasoconstriction, whereas vasoconstriction elicited by depolarizing agents is maintained. Loss of pulmonary hypoxic vasoconstriction is not linked to alterations in oxygen‐sensitive K + currents in pulmonary artery smooth muscle cells. Loss of hypoxic vasoconstriction is associated with early postnatal oxidative damage and corrected by an antioxidant diet. Perinatal hyperoxia damages carotid body chemoreceptor cell function and the antioxidant diet does not reverse it. The hypoxia‐elicited increase in erythropoietin plasma levels is not affected by perinatal hyperoxia. The potential clinical significance of the findings in clinical situations such as pneumonia, chronic obstructive pulmonary disease or general anaesthesia is considered. Abstract: Adult mammalians possess three cell systems that are activated by acute bodily hypoxia: pulmonary artery smooth muscle cells (PASMC), carotid body chemoreceptor cells (CBCC) and erythropoietin (EPO)‐producing cells. In rats, chronic perinatal hyperoxia causes permanent carotid body (CB) atrophy and functional alterations of surviving CBCC. There are no studies on PASMC or EPO‐producing cells. Our aim is to define possible long‐lasting functional changes in PASMC or EPO‐producing cells (measured as EPO plasma levels) and, further, to analyse CBCC functional alterations. We used 3‐ to 4‐month‐old rats born and reared in a normal atmosphere or exposed to perinatal hyperoxia (55–60% O2 for the last 5–6 days of pregnancy and 4 weeks after birth). Perinatal hyperoxia causes an almost complete loss of hypoxic pulmonary vasoconstriction (HPV), which was correlated with lung oxidative status in early postnatal life and prevented by antioxidant supplementation in the diet. O2 ‐sensitivity of K + currents in the PASMC of hyperoxic animals is normal, indicating that their inhibition is not sufficient to trigger HPV. Perinatal hyperoxia also abrogated responses elicited by hypoxia on catecholamine and cAMP metabolism in the CB. An increase in EPO plasma levels elicited by hypoxia was identical in hyperoxic and control animals, implying a normal functioning of EPO‐producing cells. The loss of HPV observed in adult rats and caused by perinatal hyperoxia, comparable to oxygen therapy in premature infants, might represent a previously unrecognized complication of such a medical intervention capable of aggravating medical conditions such as regional pneumonias, atelectases or general anaesthesia in adult life.